Intravenous immunoglobulin for neonatal isoimmune thrombocytopenia. Issue 7 (July 1985) - Derycke, M; Dreyfus, M; Ropert, J C; Tchernia, G
Abstract : An infant with severe, isoimmune thrombocytopenia secondary to maternal anti-Pla 1 immunisation was treated successfully by intravenous gammaglobulin (400 mg/kg per day for five days). This treatment compared with Pla 1 negative platelet transfusions is discussed.